Mr Large in charge - Murphy, Jill (London Walker Books, 2005)
Mrs Large isn t feeling well so Mr Large sends her back to bed. I ll take charge, he says. So while he and the children get busy hoovering, dusting and tidying, Mrs Large settles down for a nice rest. But with Mr Large in charge, Mrs Large s restful day is not as restful as she d hoped!
English Stories
Keywords: English stories